Demographic Influences on Screen Time: Impacts on Academic Performance and Mental Health - Diyanshi Patel; Pooja Vyas; Dhara Patel; Aryan Shah; Rahul Chauhan; Andino Maseleno; R Rizal Isnanto (International Journal of Psychology and Health Science, 2024)
This study examines the relationship between demographic factors—age, gender, and education level—and various aspects of screen time usage, including average screen time, academic performance, and associated health impacts such as anxiety and social life interactions. Using ANOVA, we found significant differences in average screen time based on age and education level, with younger and more educated individuals tending to engage more with digital devices for studying. Notably, academic performance was influenced by education level, while anxiety and social life were significantly affected by both education and age. These findings underscore the importance of considering demographic factors in understanding screen time behaviors. Future research should explore longitudinal effects and potential interventions to mitigate negative outcomes.